Evaluation of Fetal Congenital Anomalies After 23 Weeks of Gestation: Clinical Analysis of 444 Cases - Gezginç, Kazım; Karataylı, Rengin; Yazıcı, Fatma; İçen, Mehmet Sait; Acar, Ali (Gynecology Obstetrics & Reproductive Medicine, 2011)
OBJECTIVE: In this study it is objected to identify the frequency and distribution of congenital anomalies in babies born at Selçuk University Meram Medical School, Department of Obstetrics and Gynecology. STUDY DESIGN: Fetal congenital anomalies detected after 23 weeks’ of gestation from January 2008 to December 2010 were retrospectively reviewed. Fetal congenital anomalies were diagnosed prenatally or after birth. RESULTS: A total of 444 infants were diagnosed to have congenital anomalies among 7032 live and deceased newborn infants delivered between January 2008-December 2010. The mean maternal age was 27.84±6.48 years (range 15-47 years). The average gestational age at delivery was 35.32±4.5 weeks (range 22-43 weeks). Among all births, 106 infants (23.9%) had nervous system anomalies, 77 (17.3%) had multiple congenital anomalies, 68 (15.3%) had cardiovascular system anomalies, 66 (14.9%) had digestive system anomalies, 45 had (10.1%) urogenital system anomalies, 33 (7.4%) had hydrops fetalis, 17 (3.8%) had chromosomal anomalies, 13 (2.9%) had respiratory system anomalies, 12 (2.7%) had musculoskeletal system anomalies. CONCLUSION: Most of our patients preferred to continue pregnancies with congenital anomalies because of sociocultural and religious beliefs. So, reducing the incidence of congenital anomalies by controlling environmental risk factors and preconceptional care are of great importance.